Learning Strategies on Sound Materials for Phase Students with Disabilities in Extraordinary Schools - Suci Inggirina; Masri Kudrat Umar; Irsan (Universitas Muhammadiyah Palu, 2025)
This study aims to describe the implementation of sound science learning for students with disabilities in special schools. The results of the study showed that teachers started learning with greetings, prayers, and perceptions, then conveyed learning objectives and inserted ice breaking to increase students' enthusiasm for learning. In the core activity, teachers use lecture methods and learning resources in the form of powerpoint learning media (PPT) and LKPD to help students understand sound material. Teachers also pay special attention to students with disabilities by adjusting teaching styles, learning tempos, and forms of communication according to students' needs. The characteristics of visually impaired students observed were motor difficulties, limitations in communication and expression, low motivation and confidence, difficulty understanding abstract material, dependence on teacher assistance and tools, and difficulty in following the rhythm of group learning. The learning strategies used are an individualized approach, which is effective in fostering a sense of security, appreciating even the smallest effort, and guiding students to remain active in learning activities. The results of the study show that teachers have tried to adapt learning strategies to the needs of students with disabilities, but there is still a need for improvement in media use, more active interaction, and a more concrete and participatory approach to make learning more effective and in accordance with the needs of students. Thus, this research can contribute to the development of more effective learning strategies for students with disabilities in exceptional schools. The study also shows that an individualized approach can increase the motivation and confidence of students with disabilities in learning, as well as help them understand the material better. Therefore, this research can be a reference for teachers and education practitioners in developing more effective learning strategies and in accordance with the needs of students with disabilities.